Neurodegeneration with brain iron accumulation: update on pathogenic mechanisms - Levi, Sonia; Finazzi, Dario (Frontiers in Pharmacology, 2014)
Perturbation of iron distribution is observed in many neurodegenerative disorders, including Alzheimer’s and Parkinson’s disease, but the comprehension of the metal role in the development and progression of such disorders is still very limited. The combination of more powerful brain imaging techniques and faster genomic DNA sequencing procedures has allowed the description of a set of genetic disorders characterized by a constant and often early accumulation of iron in specific brain regions and the identification of the associated genes; these disorders are now collectively included in the category of Neurodegeneration with Brain Iron Accumulation (NBIA). So far 10 different genetic forms have been described but this number is likely to increase in short time. Two forms are linked to mutations in genes directly involved in iron metabolism: Neuroferritinopathy, associated to mutations in the FTL gene and Aceruloplasminaemia, where the ceruloplasmin gene product is defective. In the other forms the connection with iron metabolism is not evident at all and the genetic data let infer the involvement of other pathways: Pank2, COASY,Pla2G6, C19orf12, and FA2H genes seem to be related to lipid metabolism and to mitochondria functioning, WDR45 and ATP13A2 genes are implicated in lysosomal and autophagosome activity, while the C2orf37 gene encodes a nucleolar protein of unknown function. There is much hope in the scientific community that the study of the NBIA forms may provide important insight as to the link between brain iron metabolism and neurodegenerative mechanisms and eventually pave the way for new therapeutic avenues also for the more common neurodegenerative disorders. In this work we will review the most recent findings in the molecular mechanisms underlining the most common forms of NBIA and analyze their possible link with brain iron metabolism.